A Dutch Fanconi Anemia FANCC Founder Mutation in Canadian Manitoba Mennonites - Yne de Vries; Nikki Lwiwski; Marieke Levitus; Bertus Kuyt; Sara J. Israels; Fré Arwert; Michel Zwaan; Cheryl R. Greenberg; Blanche P. Alter; Hans Joenje; Hanne Meijers-Heijboer (Anemia)
Fanconi anemia (FA) is a recessive DNA instability disorder associated with developmental abnormalities, bone marrow failure, and a predisposition to cancer. Based on their sensitivity to DNA cross-linking agents, FA cells have been assigned to 15 complementation groups, and the associated genes have been identified. Founder mutations have been found in different FA genes in several populations. The majority of Dutch FA patients belongs to complementation group FA-C. Here, we report 15 patients of Dutch ancestry and a large Canadian Manitoba Mennonite kindred carrying the FANCC c.67delG mutation. Genealogical investigation into the ancestors of the Dutch patients shows that these ancestors lived in four distinct areas in The Netherlands. We also show that the Dutch and Manitoba Mennonite FANCC c.67delG patients share the same haplotype surrounding this mutation, indicating a common founder.